The Influence of Sustainability Reporting and Green Accounting on The Financial Reporting Performance of Manufacturing Companies Listed on The Indonesian Stock Exchange (Case Study of Manufacturing Companies in The Cosmetics and Household Goods Subsector for The Period 2021-2023) - Brigita Lona Eniyasari; As’adi; Sri Andika Putri (International Journal of Management and Business, 2026)
This study aims to examine the influence of Sustainability Reports and Green Accounting on the financial reporting performance of manufacturing companies in the cosmetics and household goods subsector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. This research employs a quantitative approach using secondary data obtained from the annual reports of each company. The results indicate that the sustainability report has a negative and significant impact on financial reporting performance. This suggests that in the short term, the disclosure of sustainability reports may require substantial operational costs, and its benefits are not immediately felt in the company's profits. Meanwhile, green accounting has a positive and significant influence on financial reporting performance. This indicates that the implementation of environmentally-based accounting practices, such as recording environmental costs and efficient waste management, contribute to improving the company's financial performance.